HUBUNGAN TINGKAT KECEMASAN DENGAN TERJADINYA INSOMNIA PADA WANITA PREMENOPAUSE DI DUSUN NGABLAK DESA KEDUNGRUKEM KECAMATAN BENJENG KABUPATEN GRESIK - Hidaayah, Nur; Alif, Hilmi (Jurnal Ilmiah Kesehatan, 2016)
The anxiety that occurs in premenopausal women causes onset insomnia, due to physical changes. Most premenopausal women are not ready to face those changes, so that if not tackled will continue on depression. The purpose of the research is to find out the relationship with the level of anxiety and insomnia in premenopausal women in Dusun Ngablak Desa Kedungrukem Kecamatan Benjeng Kabupaten Gresik. Analytic design research using the approach of cross sectional. The population was premenopausal women amounted to 80 people, a large sample of the 66 respondents taken with Simple Random Sampling technique. The independent variable and the dependent variable levels of anxiety onset insomnia. The instrument uses a sheet of the questionnaire. The data obtained were tested with Mann-Whitney with a level of significance (? = 0.05). The results showed a large majority (56.1%) experienced a mild anxiety and the majority (68.2%) experiencing insomnia. Mann-Whitney test results obtained ? = 0.000 and ? = 0.05, meaning ? then H0 ? < rejected means that there is a relationship with the level of anxiety and insomnia in premenopausal women in Dusun Ngablak Desa Kedungrukem Kecamatan Benjeng Kabupaten Gresik. Most women experience mild anxiety levels of premenopausal and most experienced insomnia. So it's recommended for premenopausal women to think positive on any changes experienced on the body, so that it can reduce anxiety and did not experience insomnia.